Development of heirfers and dairy productivity of cows, doughters of different simmental breed bulls - V. Ya. DANKIV; М. А. PETRYSHYN; Ya. Ya. PAVLYSHAK (Передгірне та гірське землеробство і тваринництво)
Scientific-economical experiment on animals of Simmental cattle combined (dairy-meat) breed was carried out in TzOV «Litynske». A retrospective analysis was conducted and the milk productivity of cows and daughters of different bulls was studied. The growth of repair heifers, half-sisters by father was studied.